Fatigue of glass reinforced plastics under complex stresses - Griffiths, John R. (1974)
Many failure theories have been postulated to predict the behaviour of glass reinforced plastics (GRP) under complex stresses. However, the efficient use of these theories for design purposes is inhibited because the experimental complex stress data needed to verify and discriminate between them is not available. This thesis presents some of the experimental data required.